1975
DOI: 10.1177/0300985875012005-00610
|View full text |Cite
|
Sign up to set email alerts
|

Age-Dependent Resistance to Transmissible Gastroenteritis of Swine: III. Effects of Epithelial Cell Kinetics on Coronavirus Production and on Atrophy of Intestinal Villi

Abstract: Abstract. Coronavirus titers in small intestine, degree of villous atrophy and apparent rates of regeneration of intestinal villi were compared in newborn, 3-week-old and adult pigs for 1 week after they were exposed to the transmissible gastroenteritis virus of swine. The response within the newborn group was homogeneous, resulting in high virus titers, maximal villous atrophy and comparatively slow regeneration. In general, virus titers were lower, villous atrophy was less severe and regeneration more rapid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
23
0

Year Published

1978
1978
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 12 publications
4
23
0
Order By: Relevance
“…Our clinical observations show that the 5-day-old pigs were more susceptible to PDCoV infection than the 21-day-old pigs. This age-dependent disease severity in PDCoV infection is consistent with previous reports of PEDV and TGEV infections (Moon et al, 1975;Shibata et al, 2000) and might be attributable to the lower turnover rate of enterocytes in 5-day-old pigs than in 21-day-old pigs during PDCoV infection, as has been described in PEDV infection . A recent report showed that an outbreak of PDCoV infection was observed in gilts and sows in Thailand (Janetanakit et al, 2016), indicating that the pathogenicity of PDCoV is not confined to piglets.…”
Section: Discussionsupporting
confidence: 91%
“…Our clinical observations show that the 5-day-old pigs were more susceptible to PDCoV infection than the 21-day-old pigs. This age-dependent disease severity in PDCoV infection is consistent with previous reports of PEDV and TGEV infections (Moon et al, 1975;Shibata et al, 2000) and might be attributable to the lower turnover rate of enterocytes in 5-day-old pigs than in 21-day-old pigs during PDCoV infection, as has been described in PEDV infection . A recent report showed that an outbreak of PDCoV infection was observed in gilts and sows in Thailand (Janetanakit et al, 2016), indicating that the pathogenicity of PDCoV is not confined to piglets.…”
Section: Discussionsupporting
confidence: 91%
“…Interestingly, unlike in newborn piglets, PDCoV infection did not cause vomiting and death in weaned piglets at a high dose (1 × 10 9 TCID 50 /head) in 7 days, indicating that newborn piglets were more susceptible to PDCoV infection than weaned piglets. This phenomenon demonstrated that PDCoV infection is another age-dependent disease severity like PEDV and TGEV (Moon et al, 1975;Isao et al, 2000). Furthermore, we collected fecal swabs from the PDCoV-challenged piglets and detected the viral fecal shedding by real-time PCR.…”
Section: Discussionmentioning
confidence: 95%
“…Rings of fixed gut were dehydrated and embedded in paraffin wax, and sections 5 pm thick were cut and stained with haematoxylin and eosin. The severity of the lesions in each of the five gut positions was estimated as the ratio, average villus length : average crypt length, calculated from measurements of the five longest complete villi and their associated crypts at each position, made with a light microscope equipped with a x 10 objective and ocular micrometer (Hooper and Haelterman, 1969;Moon, Norman and Lambert, 1973;Thake, Moon and Lambert, 1973;Moon et al, 1975). No attempts were made to measure crypts associated with Peyer's patches.…”
mentioning
confidence: 99%